Comparative government and politics an introduction - Hague, Rod.; Harrop, Martin (New York Palgrave Macmillan, 2010)
Long established as the leading text in the field, the 8th edition has been comprehensively updated and rewritten. Accessible, student-friendly and truly international in its coverage, this edition has an improved structure and new material on methodology"-- Provided by publisher.
Machine generated contents note: PART 1 CONCEPTS AND APPROACHES -- Political Concepts -- Comparative Approaches -- Comparative Methods -- PART 2 STATES AND REGIMES -- The State -- Democracy -- Authoritarian Rule -- PART 3 POLITICAL MOBILIZATION -- Political Culture -- Political Communication -- Political Participation -- Elections and Voting -- Interest Groups -- Political Parties -- PART 4 GOVERNMENT AND GOVERNANCE -- Constitutions and Law -- Multilevel Governance -- Legislatures -- The Political Executive -- Public Management and Administration -- PART 5 PUBLIC POLICY AND POLITICAL ECONOMY -- The Policy Process -- Political Economy -- PART 1 CONCEPTS AND APPROACHES -- Political Concepts -- Comparative Approaches -- Comparative Methods -- PART 2 STATES AND REGIMES -- The State -- Democracy -- Authoritarian Rule -- PART 3 POLITICAL MOBILIZATION -- Political Culture -- Political Communication -- Political Participation -- Elections and Voting -- Interest Groups -- Political Parties -- PART 4 GOVERNMENT AND GOVERNANCE -- Constitutions and Law -- Multilevel Governance -- Legislatures -- The Political Executive -- Public Management and Administration -- PART 5 PUBLIC POLICY AND POLITICAL ECONOMY -- The Policy Process -- Political Economy.
Keywords: Comparative government